PEMODELAN SISTEM PENDUKUNG KEPUTUSAN PROMOSI JABATAN PADA PERUSAHAAN ASURANSI DENGAN MENGGUNAKANMETODE FUZZY MAMDANI - soebroto, arief andy (Department of Informatics Engineering, 2014)
Promotion of professionalism is the recognition given to employees on company performance. Promotion can increase employee job satisfaction and effectiveness. Promotion opportunities can make employees feel valued, cared for, needed and recognized his ability by the company. One of the positive impact of the promotion is to produce a high loyalty to the company. However, in deciding the promotion of optimum accuracy is needed in the selection of employees eligible to get it. Factors that influence the decision of the promotion criteria should be considered as working time, discipline, teamwork, performance and appearance. The proposed research model is a decision support system in the promotion of insurance companies using fuzzy method mamdani. The method used for calculating the value of each criterion in determining preferences. The results of these calculations a reference manager in determining which employees are given proper promotion. Keywords : Decision support systems, Promotion of professionalism, Mamdani Fuzzy.